Pengukuran Konstanta Dielektrik Udara Pada Perangkat Kapasitor Plat-Sejajar Berbasis Mikrokontroler Arduino Uno - Andrian Wijayono; Valentinus Galih Vidia Putra (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2020)
This study aims to design a prototype of an air dielectric constant measuring device and be able to measure the capacitance value using an Arduino microcontroller device. The measurement of the air dielectric constant is carried out by means of the principle of measuring the capacitance of a capacitor device with a plate-parallel configuration with the air dielectric material. Capacitance measurements are carried out with the principle of charging and emptying capacitors using an Arduino Uno microcontroller device. The charging and discharging process is carried out using a series of resistor-capacitor (RC) series with a source voltage of 5 volts from the microcontroller device. This experiment has used a parallel plate with a size of 29 × 30 cm as an electrode capacitor, and a resistor device with a size of 125 megaOhm. The results showed that the behavior of charging and discharging parallel plate capacitor devices has an R square value of> 0.9, which shows a fairly good correlation between the predicted and experimental results on capacitance measurements. The results showed that the prototype of a dielectric constant measuring device can be well designed by showing the capacitance value of the device at the state of filling and emptying and the measurement results show the value of the air dielectric constant has been measured with a value of 0.991 - 1.0346.